2006
DOI: 10.1007/s00422-006-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the noise and attractor strength of coordinated limb movements using recurrence analysis

Abstract: The variability of coupled rhythmic limb movements is assumed to be a consequence of the strength of a movement's attractor dynamic and a constant stochastic noise process that continuously perturbs the movement system away from this dynamic. Recently, it has been suggested that the nonlinear technique of recurrence analysis can be used to index the effects of noise and attractor strength on movement variability. To test this, three experiments were conducted in which the attractor strength of bimanual wrist-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 68 publications
5
68
0
Order By: Relevance
“…Such an increase in asymmetry between the 2 hands could be (one of) the source(s) of the difference in pattern stability between young and older participants. Such a hypothesis is consistent with the results observed by Richardson et al [42] using cross-recurrence quantification analysis. They showed that modulations in frequency detuning between oscillatory hands influenced the magnitude of internal fluctuations and consequently relative phase variability.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Such an increase in asymmetry between the 2 hands could be (one of) the source(s) of the difference in pattern stability between young and older participants. Such a hypothesis is consistent with the results observed by Richardson et al [42] using cross-recurrence quantification analysis. They showed that modulations in frequency detuning between oscillatory hands influenced the magnitude of internal fluctuations and consequently relative phase variability.…”
Section: Discussionsupporting
confidence: 83%
“…They showed that modulations in frequency detuning between oscillatory hands influenced the magnitude of internal fluctuations and consequently relative phase variability. According to Richardson et al [42] , one could speculate that changes in frequency detuning resulted in rescaling of the magnitude of the perturbation process (i.e. noise) inherent to inter-limb coordination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with [11,12], the relative phase difference between movement signals was calculated per trial and averaged for each start condition respectively. If in-phase synchronization occurred, a peak for data in the 0-20° region should be found, for anti-phase synchronization in the 160-180° region.…”
Section: Resultsmentioning
confidence: 99%
“…The data were down-sampled for these analyses to 50 Hz. RQA measures used were percent determinism, percent recurrence, and entropy (delay = 40, embedding dimension = 4, radius = 10), and the standard largest box size was used (Richardson et al 2007). Radial sway in low-and high-frequency ranges was examined separately to assess changes in slow and fast timescales of postural control (Yeh et al 2010(Yeh et al , 2014van den Heuvel et al 2009).…”
Section: Cop Acquisition and Analysismentioning
confidence: 99%